Retinal vascular caliber associated with cardiac and renal target organ damage in never‐treated hypertensive patients. (May 2017) - Daien, Vincent; Granados, Loic; Kawasaki, Ryo; Villain, Max; Ribstein, Jean; Du Cailar, Guilhem; Mimran, Albert; Fesler, Pierre
ABSTRACT: Objective: The aim of this study was to assess the relationship between retinal vascular caliber and target organ damage in HT patients. Methods: Data were collected on cardiac, renal, vascular, and retinal variables in 88 consecutive never‐treated HT subjects. Retinal vascular calibers were measured from fundus photographs by using a semi‐automated computer‐assisted program and summarized as CRAE and CRVE. Results: Mean CRAE and CRVE were significantly lower in patients with left ventricular hypertrophy (left ventricular mass ≥110 g/m² for women, 125 g/m² for men) than in those with normal left ventricular (CRAE: 129.4±3.7 vs 138.2±2.3 μm; P =.04; CRVE: 195.6±4.4 vs 209.8±2.7 μm; P =.008). CRAE and CRVE were negatively correlated with urinary albumin excretion (β±SE=−15.4±3.2, P <.0001 and β±SE=−11.9±4.4, P =.001, respectively) but were not correlated with estimated glomerular filtration rate ( P =.21 and P =.75, respectively), carotid‐to‐femoral pulse wave velocity ( P =.24 and P =.14), or carotid augmentation index ( P =.43 and P =.16). Conclusion: In never‐treated HT patients, reduced CRAE and CRVE were associated with cardiac and renal preclinical damage, ie, left ventricular hypertrophy and albuminuria, but not estimated glomerular filtration rate or vascular stiffness.